An evaluation of functional outcome in elderly patients with proximal humeral fractures treated conservatively - Çalışal, Emre (Journal of Surgery and Medicine, 2020)
Aim: The relationship between radiological data and the clinical outcomes in elderly patients with incomplete proximal humeral fractures treated conservatively is limited and controversial in the literature. We aimed to report the short-to-mid-term results of the radiological data and functional outcome in these patients. Methods: A total of 114 patients over 65 years of age, diagnosed with unilateral isolated incomplete proximal displaced humerus fractures, and treated conservatively, were recruited in the study. Demographic characteristics, radiological data and clinical scores of all patients were recorded. Fractures were classified according to the Neer classification. Functional evaluation of patients was performed via Quick-Disabilities of Arm, Shoulder, and Hand (Quick-DASH) and Visual Analog Scale (VAS). Results: Mean VAS and Quick-DASH scores of the patients were 3.6 (1.4) and 34.5(13.7), respectively, both of which changed significantly as the number of the parts of fracture increased (P=0.02 and P=0.04, respectively). The VAS and the Quick-DASH scores were significantly higher in females (P=0.02 and P=0.03, respectively), similar among the smokers (P=0.58 and P=0.41, respectively), and significantly higher in diabetic and osteoporotic patients (P<0.001 and P=0.39, respectively). Conclusion: Functional outcomes after conservative follow-up in patients over 65 years of age with incomplete proximal humerus fractures are good in most patients. Therefore, conservative treatment can be an option regardless of the fracture type in elderly patients with incomplete proximal humeral fractures.